ANALISIS LIGNIN, SELULOSA DAN HEMI SELULOSA JERAMI JAGUNG HASIL DI FERMENTASI TRICHODERMA VIRIDE DENGAN MASA INKUBASI YANG BERBEDA - Ismail Ismail Pasue; e salah (Jambura Journal of Animal Science, 2019)
The research objective was to find out the different incubation period at the making of cron straw fermentation with Trichoderma viride based on the content of lignin, cellulse, and  hemicellulse.  The researchwas conducted based on completely randomized design (CRD) with four treatments and four replications. The treatments were fermentation P0 = cron straw without incubation; P1 =  cron straw with 1 week  incubation; P2 = cron straw with 2- week  incubation; P3 = cron straw with 3- week  incubation.  The data were analyzed by Analysis of Variance and having an advenced test using the Duncan test. The finding of researsh revealed that the fermentation of cron straw using Trichoderma viride with differnt incubation period had a significant effect (P0.01) on the content of of lignin, cellulse, and  hemicellulse. The lowest lignin content was found in treatment P2 (8.57b), the lowest cellulose content was found in treatment P0 (32.96 b), P1 (32.93 b, and P2 (32.48 b), and the lowest hemicellulose content was foud intreatment P2 (11.78 c) and P3 (12.27 c). To conlude, the best incubtiontperiod for fermentationof cron straw with Trichoderma viride was 2 weeks (treatment P2)